2010
DOI: 10.1677/erc-09-0172
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and prostate cancer

Abstract: Despite much progress in prostate cancer management, new diagnostic, prognostic and therapeutic tools are needed to predict disease severity, choose among the available treatments and establish more effective therapies for advanced prostate cancer. In the last few years, compelling evidence has documented the role of microRNAs as new broad-spectrum oncogenes or tumour suppressor genes, thus their use as diagnostic, prognostic and therapeutic biomolecules is envisaged. This review extensively and critically sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 156 publications
3
127
0
4
Order By: Relevance
“…MiR-141 is found upregulated in primary tissues in a variety of studies including ours (2,25), and inclusion of miRNA expression data significantly improves the accuracy of markers like prostatespecific antigen in the diagnosis or prediction of tumor outcome (33). The induction of the miR-106b-93-25 cluster is in line with the poor prognosis described by others (34).…”
Section: Discussionmentioning
confidence: 81%
“…MiR-141 is found upregulated in primary tissues in a variety of studies including ours (2,25), and inclusion of miRNA expression data significantly improves the accuracy of markers like prostatespecific antigen in the diagnosis or prediction of tumor outcome (33). The induction of the miR-106b-93-25 cluster is in line with the poor prognosis described by others (34).…”
Section: Discussionmentioning
confidence: 81%
“…At present, consistent data regarding alterations in the expression of miRNA in PCa are still limited (reviewed by Coppola et al, 2010) and studies addressing the genome-wide expression profiling of other small ncRNA in this malignancy are lacking. Here, we utilized Solexa Illumina Deep Sequencing to examine the entire spectrum of small ncRNA in PCa specimens, and further screened for changes in the expression of 723 miRNAs by microarray-profiling of 102 histologically confirmed malignant and non-malignant samples from prostatectomy, lymph node and TURP origin.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs miRNAs regulate normal processes of growth and development as well as pathogenic processes associated with cancer, and analyses of their expression patterns have been effective for stratifying human cancers (Lu et al 2005;Volinia et al 2006). Expression profiling studies of human prostate tumors and xenografts have suggested that the expression patterns of miRNAs may distinguish indolent from aggressive tumors (Porkka et al 2007;Ambs et al 2008;Ozen et al 2008;Coppola et al 2009;DeVere White et al 2009), and have implicated specific miRNAs in castration-resistant prostate cancer Sun et al 2009). Consistent with these findings, key enzymatic components of miRNA synthesis and processing such as Dicer are up-regulated during prostate tumor progression (Chiosea et al 2006;Ambs et al 2008;Poliseno et al 2010a), while functional analyses of mice with conditional deletion of Dicer support a role for miRNAs in prostate epithelial proliferation .…”
Section: Ezh2mentioning
confidence: 99%